Analisis Kebijakan Pengembangan SDM Terhadap Kualitas Sumber Daya Aparatur Pada Dinas Pemuda Olahraga dan Seni - Mattarima Mattarima; Roswiyanti Roswiyanti (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
The aim of the research is to determine the level of capability of the Human Resources (HR) apparatus at the Maros Regency Youth Sports and Arts Service (DISPORI). And to find out the policies for developing human resources for personnel at the Maros Regency Youth Sports and Arts Service (DISPORI). The research methods used are quantitative and qualitative research methods. The results of the research are that the Human Resources development policy for the apparatus at the Maros Regency Youth, Sports and Arts Service has been running well in accordance with applicable personnel procedures and regulations. This can be seen from the implementation of the HR development policy for personnel at the Maros Regency Youth, Sports and Arts Service. The policy of developing human resource capabilities for the apparatus has goals and objectives, namely development and improvement as well as carrying out the main tasks and functions as government officials so that they can meet predetermined standards while being able to make decisions independently and professionally based on a spirit of service and changes in attitudes that lead to further development. openness, attitude of serving and protecting the public as the main duties and responsibilities.